Towards the adaptation of SAwD for Deaf Users: Pilot S essions with the Stakeholders Identification Diagram - Prietch, Soraia S.; Sánchez, J. Alfredo; Ferreira, Priscilla Lopes; Fabris, José Augusto; Leite, Vanuza Martins; Alves, Daniel Domingos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Our work focuses on the inclusion of deaf users in participatory design approaches. This entails not only increased awareness of the diversity of participants, but also the use of appropriate research instruments. In existing and novel research artifacts found in the literature, not only the language, but also how deaf persons rely on a spatial and visual way for thinking, acting, representing ideas, and interacting, become key factors for autonomous participation. In this paper, we present three phases of our research journey, namely, contextualization, ideation and redesign, and evaluation of a proposed adaptation of the Stakeholder Identification Diagram (SID) artifact, used in the Socially Aware Design approach. Twenty research sessions were carried out with and by a group of deaf and hearing codesigners: Sixteen virtual meetings with the research team, and four face-to-face pilot sessions. The evaluation phase took twelve sessions in total since we had to go back and iterate with the contextualization phase. Also, after pilot sessions, we met to analyze results and discuss previous phases. Various alternatives for adaptations in the layout and in the way of using the instrument were ideated and discussed before reaching a first version to be tested in pilot sessions. This work presents three main contributions: the three-phase framework to adapt research artifacts by working with a team of diverse profile and educational background, the collaboration between deaf and hearing researchers as codesigners in the field of HCI in Brazil, and the adaptation of the SID artifact to consider deaf participants. To the best of our knowledge, neither of the last two contributions have been previously explored. We aim to generalizing our adaptation process to other instruments for working with deaf researchers and participants.